Correlation between array-comparative genomic hybridization-defined genomic gains and losses and survival: identification of 1p31-32 deletion as a prognostic factor in myeloma - Chng, WJ (2010)
In this study, we correlated array-comparative genomic hybridization-defined abnormalities with survival in two different cohorts of patients treated with therapy based on high-dose melphalan with autologous stem-cell transplantation (64 from the Mayo Clinic and 67 from the University of Arkansas Medical School) and identified that several regions of genomic gains and losses were significantly associated with poorer survival. Three noncontiguous survival relevant regions covering 1p31-33 and two noncontiguous regions covering 20p12.3-12.1 were common between the two datasets. The prognostic relevance of these hotspots was validated in an independent cohort using fluorescent in situ hybridization, which showed that 1p31-32 loss is significantly associated with shorter survival (24.5 months versus 40 months, log-rank P-value=0.01), whereas 20p12 loss has a trend toward shorter survival (26.3 months versus 40 months, log-rank P-value=0.06). On multivariate analysis, 1p31-32 loss is an independent prognostic factor. On further analysis, the prognostic impact of 1p31-32 loss is due to shortening of post-relapse survival as there is no impact on complete response rates and progression-free survival.